Technology Transformation: Promoting Sustainable Indonesia MSMEs and Cooperative by Digitalization - Andjarwati, Tri; Wulan, Vieqi Rakhma (Universitas Negeri Semarang, 2021)
This research was conducted to find out what steps the government has taken in striving for society to be 'digital literate', what obstacles are faced and what digital forms have been implemented by MSME players and cooperatives that have gone digital. The method used is an integrative review. The results of this study found that the government has tried various ways to make SMEs and cooperatives more “digitally literate”, from infrastructure, training to collaborating with related institutions and companies that have gone online first in terms of systems of operational (transaction), marketing and also payment. Obstacles to infrastructure and available facilities as well as the lack of information and human resource skills in utilizing digital are challenges faced by the government, SMEs and cooperatives. Therefore, better coordination from up to bottom is needed so that understanding and utilization of digital can be distributed evenly. For MSMEs and cooperatives that have “go digital”, found that they are still at the basic and intermediate levels, while the platforms used are still in the sharing economy, e-commerce, social media, cloud computing and other digital platforms related to applications to simplify transactions and operations.